Antibacterial Activity of Turmeric Rhizome Extract (Curcuma longa Linn.) Against Staphylococcus aureus: A Systematic Literature Review - Nurhayani; Eko Avianto (HM Publisher, 2022)
Staphylococcus aureus is a normal flora that exists in the upper respiratory tract but can cause infection if found in amounts that are more than the normal limit (>110 CFU/ml). One of the herbal medicinal plants that is widely used in Indonesia is turmeric (Curcuma longa Linn.). Turmeric rhizome (Curcuma longa Linn.) contains active substances that have antibacterial properties, such as curcumin, flavonoids, alkaloids, saponins, and tannins. To determine the antibacterial activity of turmeric (Curcuma longa Linn.) rhizome extract against the growth of Staphylococcus aureus bacteria. This research method is a literature review study. Data collection techniques through Google Scholar, Science Direct, and Pubmed with a time limit of the last 5 years will be eliminated according to the restriction criteria. There were 2005 articles that were found and then excluded according to the restriction criteria. 15 articles were found to be reviewed. Turmeric rhizome extract (Curcuma longa Linn.) has antibacterial activity against Staphylococcus aureus bacteria.